2018
DOI: 10.3748/wjg.v24.i36.4186
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, types, and treatment of anemia in Turkish patients with inflammatory bowel disease

Abstract: AIMTo specify the type and prevalence of anemia along with a treatment approach for inflammatory bowel disease (IBD).METHODSWe conducted a retrospective study on 465 patients who were diagnosed with IBD and followed up at our hospital from June 2015 to June 2016 [male: 254, female: 211; average age: 47 ± 14.4; Crohn’s disease (CD): 257, Ulcerative Colitis (UC): 208]. Epidemiological and clinical data, such as sex, age, age of diagnosis, type of IBD, disease extension, disease behavior and duration, treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
6
12
0
6
Order By: Relevance
“…The present study showed that the frequency of anemia in Greek IBD patients followed at tertiary referral centers is 49.3% meaning that almost half of those patients experience anemia, which is similar to previous reports from other countries ( 2 , 13 16 ). Anemia was present more frequently in CD patients and in females which is also in accordance to other studies ( 13 , 15 , 17 ). It is of notice that there were few patients (6.5%) with anemia diagnosed more than one year before IBD diagnosis, whereas anemia was diagnosed at IBD diagnosis or less than one year before in 39.2% of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that the frequency of anemia in Greek IBD patients followed at tertiary referral centers is 49.3% meaning that almost half of those patients experience anemia, which is similar to previous reports from other countries ( 2 , 13 16 ). Anemia was present more frequently in CD patients and in females which is also in accordance to other studies ( 13 , 15 , 17 ). It is of notice that there were few patients (6.5%) with anemia diagnosed more than one year before IBD diagnosis, whereas anemia was diagnosed at IBD diagnosis or less than one year before in 39.2% of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with Crohn's disease frequently present vitamin deficiencies such as vitamin B9 (Folate) and vitamin B12, as reported in many studies around the world [15][16][17][18][19] and recently confirmed in a review of meta-analyses by Piovani et al 40 . Folate deficiencies in patients were associated with greater disease activity in a Spanish cohort 19 .…”
Section: Discussionmentioning
confidence: 74%
“…The level of folate and other methyl-donor molecules intake through the diet were associated to the regulation of DNA methylation. Even more significantly, serum B12 and folate (B9) deficiencies have frequently been noticed in different cohorts of IBD patients [14][15][16][17][18][19][20] . Based on the known roles of these molecules in one-carbon metabolism, epigenetic modifications such as DNA methylation profiles and modified genes expression observed in CD patients could be the result, in part, of methyl-donor molecules deficiencies.…”
mentioning
confidence: 99%
“…Nadalje, liječenje je ovisno o proširenosti i aktivnosti bolesti te prisutnosti intestinalnih i ekstraintestinalnih komplikacija. Najveći stupanj komorbiditeta s UBC ima anemija, koja negativno utječe na kvalitetu života, smanjuje radnu sposobnost i pridonosi smrtnosti oboljelih (11,12). Prema definiciji Svjetske zdravstvene organizacije, kod odraslih je muškaraca anemija prisutna ako je koncentracija hemoglobina manja od 130 g/L, a kod žena ako je koncentracija hemoglobina manja od 120 g/L.…”
Section: Uvodunclassified
“…Unsaturated Iron Binding Capacity) ili nezasićeni (slobodni) transferin za koji nije vezano željezo, transferina, saturacije transferina, feritina, eritrociti, hemoglobin, hematokrit, MCV ili prosječni volumen eritrocita, MCH ili prosječna količina hemoglobina u eritrocitu, MCHC ili prosječna koncentracija hemoglobina u eritocitima, retikulociti, te vrijednost CRP ili C-reaktivnog proteina. Dijagnoza sideropenične anemije postavljena je temeljem sljedećih kriterija: razina hemoglobina < 13 g/dL za muškarce, < 12 g/dL za žene, TfS< 20 %, razina feritina< 30 ng/mL, a zasićenost transferina (TSAT) < 16 %, MCH < 27 pg, MCV < 80 (12). Dijagnoza anemije kronične bolesti postavljena je temeljem sljedećih kriterija: razina hemoglobina < 13 g/dL, < 12 g/dL za žene, TfS< 20 %, CRP vrijednosti povišene uz TSAT < 16 % i feritin u intervalu 30 -100 ng/mL (12).…”
Section: Ispitanici I Metodeunclassified